Незалежність судді - правова і соціальна цінність - Полянський, Юрій Євгенович; Полянский, Юрий Евгеньевич; Poljanskij, Jurij (My University, 2011)
Actual aspects of independence guaranteeing of common jurisdiction courts are scrutinized in the article. Judge's independence essence is analyzed as legal institution and social value, correlation of judge's independence and court autonomy, judicial discretion are researched. Provisions of international and European law concerning judge's independence, decisions of European Court on Human Rights are commented, the prospects of their consideration in national legislation on judge's status are investigated. The essence of several judge's independence guarantees, having interior and exterior character, are exposed. Necessity of limitation judicial immunity due to recommendations of Venice Commission is substantiated, likewise reasonability of material responsibility for inflicted harm.
Полянський Ю. Є. Незалежність судді - правова і соціальна цінність / Ю. Є. Полянський // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C.80-90.
Keywords: незалежність суддів; суддівський розсуд; суддівський імунітет; независимость судей; судейское усмотрение; судейский иммунитет; judicial independence; judicial discretion; judicial immunity